2007
DOI: 10.1093/nar/gkm991
|View full text |Cite
|
Sign up to set email alerts
|

Rho-independent transcription terminators inhibit RNase P processing of the secG leuU and metT tRNA polycistronic transcripts in Escherichia coli

Abstract: The widely accepted model for the processing of tRNAs in Escherichia coli involves essential initial cleavages by RNase E within polycistronic transcripts to generate pre-tRNAs that subsequently become substrates for RNase P. However, recently we identified two polycistronic tRNA transcripts whose endonucleolytic processing was solely dependent on RNase P. Here we show that the processing of the secG leuU and metT leuW glnU glnW metU glnV glnX polycistronic transcripts takes place through a different type of m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
3

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(117 citation statements)
references
References 40 publications
(59 reference statements)
7
107
3
Order By: Relevance
“…and cspA mRNAs also indicate that the Rne-1 protein retains a significant amount of residual activity at the nonpermissive temperature, a conclusion also supported by the analysis of tRNA processing by Mohanty and Kushner (2008). In contrast, the half-lives of the rpsT (rpsT P1 and rpsT P2 ) and cspE transcripts did not change significantly among the rneD1018/rne-1, rneD1018/rng-219, and rneD1018/rng-248 strains under any condition tested (Table 3), supporting previous results that other ribonucleases such as RNase G and RNase Z can initiate the decay of these transcripts (Ow et al 2003;Perwez and Kushner 2006).…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…and cspA mRNAs also indicate that the Rne-1 protein retains a significant amount of residual activity at the nonpermissive temperature, a conclusion also supported by the analysis of tRNA processing by Mohanty and Kushner (2008). In contrast, the half-lives of the rpsT (rpsT P1 and rpsT P2 ) and cspE transcripts did not change significantly among the rneD1018/rne-1, rneD1018/rng-219, and rneD1018/rng-248 strains under any condition tested (Table 3), supporting previous results that other ribonucleases such as RNase G and RNase Z can initiate the decay of these transcripts (Ow et al 2003;Perwez and Kushner 2006).…”
Section: Discussionsupporting
confidence: 52%
“…In addition, rne-1 strains retain a significant amount of residual RNase E activity at 44 o C (Mohanty and Kushner 2008). Thus, the rneD1018/rng-219 and rneD1018/ rng-248 strains provided a means to test if the initiation of endonucleolytic decay of specific mRNAs was absolutely dependent on the presence of RNase E. For our analysis, we determined the half-lives of four mRNAs previously demonstrated to decay in an RNase E-dependent fashion (rpsO, rpsT, cspA, and cspE) (Mackie 1991;Hajnsdorf et al 1994;Perwez and Kushner 2006;Hankins et al 2007).…”
Section: The Absence Of Rnase E Differentially Affects the Decay Of Smentioning
confidence: 99%
See 1 more Smart Citation
“…12 It has been suggested that Rho-independent transcription terminators inhibit the RNase P processing step. 33 However, based on the in vivo data presented here (Fig. 4), where we compared the efficiency of the processing of constructs with and without the Rho-independent terminator, its presence does not appear to have any significant effect on the processing of the tRNA precursor.…”
mentioning
confidence: 82%
“…coli RNase E is involved in the initial processing of many tRNA transcripts, providing substrates for final maturation by RNase P and 3 0 exoribonucleases (Li and Deutscher 2002;Mohanty and Kushner 2007;Mohanty and Kushner 2008;Ow and Kushner 2002). E. coli RNase E is also required for the maturation of tmRNA (Lin-Chao et al 1999).…”
Section: Construction Of An Ncgl2281 Knockout Mutant Strainmentioning
confidence: 99%